Comparison of physicochemical properties of soils under contrasting land use systems in Southwestern Nigeria - Watanabe, Y.; Kikuno, H.; Asiedu, Robert; Masunaga, T.; Wakatsuki, T. (Japan International Research Center for Agricultural Sciences, 2015)
Soil physicochemical properties were determined for soils under cropland and forest at the headquarters of the International Institute of Tropical Agriculture in Ibadan, Southwestern Nigeria to examine the 30-year effects of different land use on the fertility of five soil series toposequences underlain by a Basement Complex. The cropland had been under cultivation for 30 years, during which mainly maize and yams had been cultivated in rotation with application of chemical fertilizer and intermittent fallow, while the forest had secondary vegetation that had been regenerated during a 30-year period under protection. The findings for cropland indicated an accumulation of available phosphorus and exchangeable potassium, soil compaction and slight depletion of topsoil organic carbon content; and the findings for forest indicated soil acidification and accumulation of exchangeable Ca at the surface soil horizon. These findings suggest the possibility of maintaining soil fertility with a long-term intensive and continuous crop farming system in kaolinitic Alfisol soil over the inland valley toposequences of tropical Africa.